1988
DOI: 10.1159/000195391
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance to Tartrazine in Aspirin-Induced Asthma: Results of a Multicenter Study

Abstract: One hundred and fifty-six German, Italian and Polish patients with confirmed aspirin-induced asthma underwent open oral challenges with increasing doses of tartrazine up to 25 mg. All positive challenges were repeated under double-blind conditions. Only 4 of 156 patients (all Polish) had positive reactions in a double-blind test, as evidenced by a fall in FEV1 > 25% from baseline and corresponding clinical symptoms. Sixty-five patients who tolerated 25 mg tartrazine well received 50–3,000 mg tartraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Tartrazine has been frequently linked to different illnesses such as chronic urticaria (CU) and asthma [7][8][9][10][11][12]. In addition, cases of angioedema, of purpura, exacerbation of atopic dermatitis and gastrointestinal symptoms related to tartrazine have been reported [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Tartrazine has been frequently linked to different illnesses such as chronic urticaria (CU) and asthma [7][8][9][10][11][12]. In addition, cases of angioedema, of purpura, exacerbation of atopic dermatitis and gastrointestinal symptoms related to tartrazine have been reported [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…• Challenge studies (Corder and Buckley, 1995;David, 1987;Devlin and David, 1992;GrzelewskaRzymowska et al, 1986;Hong et al, 1989;Jimenez-Aranda et al, 1996;Kemp and Schembri, 1985;Marques et al,1995;Montano and Orea, 1989;Morales et al, 1995;Rowe, 1988Rowe, ,1994Schulte-Korne et al, 1996;Timberlake et al, 1992;van Bever et al, 1989;Virchow et al, 1988;Wilson and Scott,1989) • Reviews (Collins-Williams, 1985;Simon, 1986;Wuthrich, 1993).…”
Section: Hypersensitivity and Intolerancementioning
confidence: 99%
“…According to results of various surveys, in some aspirin intolerant patients, tartrazine -a yellow azobenzene dye widely used for colouring drinks, foods, drugs and cosmetics -precipitated bronchoconstriction and other symptoms similar to those caused by analgesics with anti-COX activity at different rates [9,52,[54][55][56]. In the earlier studies, provocation with tartrazine in aspirin intolerant asthmatics caused bronchospasm at a rate of 7.5 -15% [9, 52,54].…”
Section: Paracetamol and Tartrazine Intolerancementioning
confidence: 99%
“…In the earlier studies, provocation with tartrazine in aspirin intolerant asthmatics caused bronchospasm at a rate of 7.5 -15% [9, 52,54]. However, recent studies showed a bronchospasm rate of 0 -2.6% after provocation with tartrazine in patients with aspirin intolerant asthma [55,56]. In the large series of studies conducted by Stevenson et al (involving 150 aspirin intolerant asthmatic patients), although the positive response rate after giving tartrazine at doses of 25 and 50 mg was 4%, the response rate was negative in all of them after repeating the test in a double-blind, placebo-controlled fashion [56].…”
Section: Paracetamol and Tartrazine Intolerancementioning
confidence: 99%